Características clínico-epidemiológicas de pacientes adultos con enfermedad renal crónica no usuarios de diálisis - Camones Iparraguirre, Elsa Nereida (2016)
Chronic Kidney Disease ( CKD ) is a growing public health problem because their main causes lie in high-prevalence disorders such as aging, high blood pressure and diabetes mellitus. In Peru, although there are no official statistics, it is estimated that about 300,000 people suffer from CKD and figures available are basically related to the last phase. Objective: Describe the clinical and epidemiological characteristics in adult patients with CKD not on dialysis users Regional Hospital of Trujillo between 2009-2013. Methods: A descriptive, retrospective cross-sectional study, where the medical records of patients with CKD who were treated during the period indicated was conducted to review. To establish the relation between the variables used chi square test (x2). Results and conclusions: The average age was 66 years, with a predominance of male over 60 years. 81 % were patients with hypertension, type 2 diabetes 43% and 38 % both. The predominant stadium was the III (44%), followed by stage IV (38%). The 56 % receive Nephroprotection with ACE inhibitors or ARBs. 94% were patients with disease diagnosis time between 0-5 years. Statistically significant relationship between stage of chronic kidney disease and hypertension age group was found